Effects of cattle manure and sludge vermicompost on nutrient dynamics and yield in strawberry cultivation with distinct continuous cropping histories in a greenhouse - Bai, Xiaofeng; Lu, Wei; Xu, Jin; Li, Qingyun; Xue, Zhanjun; Wang, Xin-Xin (Frontiers in Plant Science, 2025)
Continuous cropping has emerged as a significant challenge affecting yield and quality in greenhouse strawberries, particularly as the cultivation of strawberries as a protected crop continues to increase. To address this issue, substrates with 0 or 2 years of continuous cropping were fertilized with two types of organic materials: vermicompost derived from either sludge or cattle manure. A control group consisted of substrate without the addition of vermicompost. Both type of vermicompost improved substrate fertility, promoted plant growth and fruit quality. The cattle manure vermicompost had a better improvement effect at peak fruiting stage. Substrate nutrients were increased 14.58~38.52% (0-year substrate) and 12.04%~42.54% (2-year substrate), respectively. In both substrate types, there was a substantial increase in microbial population and enzyme activity, accompanied by a significant decrease in phenolic acid content. During the senescence stage, the use of cattle manure vermicompost led to enhancements in plant height, leaf area, and root length, with increases ranging from 15.01% to 32.77% and 23.75% to 32.78% across the two substrate types compared to the control group. Furthermore, the application of cattle manure vermicompost significantly improved both fruit yield and quality. Compared with the control (CK), the cattle manure vermicompost increased fruit yield by 18.29% and 19.64% in the 0- and 2-year substrates, respectively. The contents of soluble sugars, vitamin C, and free amino acids in the fruits increased by 21.42%~34.16% (0-year substrate) and 9.62%~42.62% (2-year substrate), at peak fruiting stage. Cattle manure vermicompost application to the 2-year substrate ranked higher in the membership function than the CK treatment at 0-year planting. In conclusion, the application of vermicompost can significantly improve strawberry fruit yield and quality, as well as substrate characteristics, thus effectively addressing challenges associated with continuous cropping. Furthermore, the use of cattle manure vermicompost produced more pronounced positive effects.